Identification of QTLs and allelic effect controlling lignan content in sesame (Sesamum indicum L.) using QTL-seq approach - Kim, Sungup; Lee, Eunsoo; Lee, Jeongeun; An, Yeon Ju; Oh, Eunyoung; Kim, Jung In; Kim, Sang Woo; Kim, Min Young; Lee, Myoung Hee; Cho, Kwang-Soo (Frontiers in Genetics, 2023)
Sesame (Sesamum indicum L.), an oilseed crop, is gaining worldwide recognition for its healthy functional ingredients as consumption increases. The content of lignans, known for their antioxidant and anti-inflammatory effects, is a key agronomic trait that determines the industrialization of sesame. However, the study of the genetics and physiology of lignans in sesame is challenging, as they are influenced by multiple genes and environmental factors, therefore, the understanding of gene function and synthetic pathways related to lignan in sesame is still limited. To address these knowledge gaps, we conducted genetic analyses using F7 recombinant inbred line (RIL) populations derived from Goenbaek and Gomazou as low and high lignin content variants, respectively. Using the QTL-seq approach, we identified three loci, qLignan1-1, qLignan6-1, and qLignan11-1, that control lignan content, specifically sesamin and sesamolin. The allelic effect between loci was evaluated using the RIL population. qLignan6-1 had an additive effect that increased lignan content when combined with the other two loci, suggesting that it could be an important factor in gene pyramiding for the development of high-lignan varieties. This study not only highlights the value of sesame lignan, but also provides valuable insights for the development of high-lignan varieties through the use of DNA markers in breeding strategies. Overall, this research contributes to our understanding of the importance of sesame oil and facilitates progress in sesame breeding for improved lignan content.